Multimodal Surgical and Medical Treatment for Extensive Rhinocerebral Mucormycosis in an Elderly Diabetic Patient: A Case Report and Literature Review - Paola Di Carlo; Roberto Pirrello; Giuliana Guadagnino; Pierina Richiusa; Antonio Lo Casto; Caterina Sarno; Francesco Moschella; Daniela Cabibi (Case Reports in Medicine)
Diabetes is a well-known risk factor for invasive mucormycosis with rhinocerebral involvement. Acute necrosis of the maxilla is seldom seen and extensive facial bone involvement is rare in patients with rhino-orbital-cerebral mucormycosis. An aggressive surgical approach combined with antifungal therapy is usually necessary. In this report, we describe the successful, personalized medical and surgical management of extensive periorbital mucormycosis in an elderly diabetic, HIV-negative woman. Mono- or combination therapy with liposomal amphotericin B (L-AmB) and posaconazole (PSO) and withheld debridement is discussed. The role of aesthetic plastic surgery to preserve the patient’s physical appearance is also reported. Any diabetic patient with sinonasal disease, regardless of their degree of metabolic control, is a candidate for prompt evaluation to rule out mucormycosis. Therapeutic and surgical strategies and adjunctive treatments are essential for successful disease management. These interventions may include combination therapy. Finally, a judicious multimodal treatment approach can improve appearance and optimize outcome in elderly patients.